Does Piezosurgery Influence the Severity of Neurosensory Disturbance Following Bilateral Sagittal Split Osteotomy?. Issue 4 (June 2019) - D'Agostino, Antonio; Favero, Vittorio; Lanaro, Luca; Zanini, Matteo; Nocini, Pier Francesco; Trevisiol, Lorenzo
Abstract : Abstract: The present paper aims to evaluate the long-term incidence and severity of the neurosensory disturbance (NSD) of the inferior alveolar nerve following bilateral sagittal split osteotomy (BSSO) of the mandibular ramus performed with piezosurgery. A retrospective study on patients referred to the Maxillofacial Surgery and Dentistry Clinic of the University of Verona for orthognathic surgery between March 2013 and October 2015 was performed. Inclusion criteria were having undergone BSSO with piezosurgery and follow-up lasting at least 24 months. Exclusion criteria were history of surgical infection, osteosynthesis failure or re-do surgery. The extent of mandibular repositioning movements was retrieved and patients underwent 4 clinical neurosensory tests. Descriptive statistical analysis was performed. 52 patients met the inclusion criteria. Average follow-up was 40 months (range 24–75). 83% of the nerves examined have no or slightly altered sensitivity. Seventy-one percent of patients perceive a moderate to none discomfort and none describes the discomfort as serious (Visual Analogue Scale [VAS] >7). The extent of mandibular repositioning did not have significant influence on the development and severity of the NSD. Resulting data led the Authors to infer that using piezosurgery in BSSO, the severity of the NSD of inferior alveolar nerve is reduced, but the incidence of permanent nerve lesions remains unchanged, compared to historical controls. Abstract : Supplemental Digital Content is available in the text